GAGASAN CERITA PANJI SEBAGAI ASPEK KETELADANAN - nurcahyo, henri (LPPM Universitas PGRI Adi Buana Surabaya, 2018)
The Panji story is a popular cultural heritage during the Majapahit period, spreading to various regions andcountries of Southeast Asia. Panji's story is not just a romantic story of Panji Asmarabangun with Dewi Sekartajibut has many interesting aspects that can be studied from various sides. There are many fairy tales that tell the story ofPanji, as well as the performing arts of tradition, art, the art of chanting, and even the Panji Story enshrined in reliefsof dozens of temples in East Java and hundreds of manuscripts of Panji scattered in various countries. From thevarious stories of Panji is contained noble values that can be a role model in the life of society and state. In the story ofPanji there is a load of courage, heroism, unyielding spirit, creativity in running tactics, caring for others, love animalsand flora, not vengeance, do not apply cruelly, love to study, devoted to mother, love and master various art and so on. The Panji is an ideal figure so much is personified by many Kings throughout history. The story of the Panji becomesintertwined between fairy tales and facts. The Panji story becomes a myth that eventually becomes a reference in life. Infact, the example of the Panji Story is not only reflected in its traits as a person but the moral of the story contained init, as well as the inspiration that can be picked as a raw material for the creation of artwork and also the creativeeconomy.